Workshop Information System Design Using Dynamic System Development Method - Alpiyasin, Feri; Febriani, Githa (Jurnal Computech & Bisnis (e-journal), 2024)
A practical and comprehensive information system is essential for operating contemporary auto repair shops, such as Madju Motor Auto Repair Shop in Bandung. This thesis aims to create and implement an information system that can enhance service efficiency and streamline data administration at the shop. This research employs the Dynamic System Development Method (DSDM), renowned for its emphasis on adaptable and user-centric software development. This study involves multiple steps, which include requirements analysis, system design, implementation, and testing. The outcome of this study is establishing an information system that allows clients to arrange car repair appointments conveniently. The system also enables the management to oversee the data that supports the shop's business processes and track the overall performance of the shop. The utilization of the DSDM methodology enables adaptability in system development, facilitating the incorporation of modifications and enhancements by evolving company requirements and customer preferences. This thesis aims to substantially improve Madju Motor Auto Repair Shop in Bandung substantially, enhancing customer service quality and operational efficiency.